Provision and Implementation of Inclusive Education in Early Childhood Centers: A Comparative Case Study of Two Semarang-Based Institutions - Khotimah, Nur; Sutarto, Joko; Diana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
The present research aims to investigate and describe the provision of inclusive education services in early childhood education institutions, focusing on TK Hj. Isriati Baiturrahman 2 and PAUD Lab School UNNES in Semarang, Indonesia. Utilizing a qualitative descriptive case study approach, the study comprehensively examined various aspects, including curriculum, student demographics, educator training, infrastructure, and financing. Key findings indicate the utilization of a collaboratively developed